2016
DOI: 10.31436/iiumej.v17i2.569
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Neuro-Fuzzy Terminal Sliding Mode Control Method With Application to Atomic Force Microscope

Abstract: In this paper, a neuro-fuzzy fast terminal sliding mode control method is proposed for controlling a class of nonlinear systems with bounded uncertainties and disturbances. In this method, a nonlinear terminal sliding surface is firstly designed. Then, this sliding surface is considered as input for an adaptive neuro-fuzzy inference system which is the main controller. A proportinal-integral-derivative controller is also used to asist the neuro-fuzzy controller in order to improve the performance of the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…By comparing ( 4), (23), and substituting Hð0Þ ≡ β, τ ≡ w d ðtÞ, _ q ≡ � e v ðtÞ into (9) it can be concluded that…”
Section: Computed Torque Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing ( 4), (23), and substituting Hð0Þ ≡ β, τ ≡ w d ðtÞ, _ q ≡ � e v ðtÞ into (9) it can be concluded that…”
Section: Computed Torque Methodsmentioning
confidence: 99%
“…The SMC design is based on a converging sliding surface and guaranteed system stability by selecting proper control coefficients. 22,23 SMC is a good solution for nonlinear systems but can cause chattering phenomena in actuators, energy dissipation, and oscillating errors. Also to have a robust behavior, SMCs need the bounds of system unknown uncertainties which is a big limitation.…”
Section: Introductionmentioning
confidence: 99%